2023
DOI: 10.1021/acs.orglett.3c02442
|View full text |Cite
|
Sign up to set email alerts
|

Nickel/SKP-Catalyzed Markovnikov Regio- and Enantioselective Hydroamination of Vinylarenes with Hydroxylamines

Chengdong Wang,
Xingheng Wang,
Zheng Wang
et al.

Abstract: A Ni-catalyzed enantioselective hydroamination of vinylarenes has been developed, affording a wide variety of α-branched chiral alkylamines in good yields with exclusive Markovnikov regioselectivity and excellent enantioselectivity. The SKP ligand was found to be crucial to both the reactivity enhancement and enantiocontrol of the reaction. The synthetic utility of the protocol was exemplified in a gram-scale reaction and late-stage modification of medicinally relevant molecules. The deuterium-labeling experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
“…Recently, metal hydride-catalyzed hydrofunctionalization of alkenes has attracted considerable attention. It has been reported that some NiH complexes demonstrate robust catalytic activity for enantioselective C–N bond-forming processes, wherein O-benzoyl hydroxylamines (BzO–NR 2 ) are used as electrophilic amination reagent which is compatible to the presence of reductant reagents in the reaction system . Accordingly, we commenced our studies on the Ni-catalyzed model reaction of phenylbutadiene 1a and morpholino benzoate 2a , and a preliminary parameter survey revealed that the reaction was best run at rt in 2-Me-THF with Ni­(COD) 2 as the Ni source in the presence of trimethoxysilane and K 2 CO 3 (for details, see SI).…”
Section: Resultsmentioning
confidence: 99%
“…In that same year, Ding and his colleagues made significant breakthroughs by unveiling a Ni-catalyzed enantioselective hydroamination procedure tailored for vinylarenes ( Scheme 19 ). 79 This approach was instrumental in the streamlined synthesis of a vast array of α-branched chiral alkylamines. The method's standout feature was its unique Markovnikov regioselectivity paired with unparalleled enantioselectivity.…”
Section: Advancements In Asymmetric Hydroamination and Hydroamidation...mentioning
confidence: 99%
“…The SKP ligand was found to be crucial for receiving exclusive Markovnikov regioselectivity and excellent enantioselectivity (Scheme 15). 34…”
Section: Introductionmentioning
confidence: 99%